If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -3) = 18 + x Reorder the terms: 8(-3 + x) = 18 + x (-3 * 8 + x * 8) = 18 + x (-24 + 8x) = 18 + x Solving -24 + 8x = 18 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -24 + 8x + -1x = 18 + x + -1x Combine like terms: 8x + -1x = 7x -24 + 7x = 18 + x + -1x Combine like terms: x + -1x = 0 -24 + 7x = 18 + 0 -24 + 7x = 18 Add '24' to each side of the equation. -24 + 24 + 7x = 18 + 24 Combine like terms: -24 + 24 = 0 0 + 7x = 18 + 24 7x = 18 + 24 Combine like terms: 18 + 24 = 42 7x = 42 Divide each side by '7'. x = 6 Simplifying x = 6
| 11a+10=0 | | x^2-.06x+.24=0 | | x-(20)*0.5=(x)*0.5+20 | | -1=1.6b+3.8 | | 2x^2-.12x+.48=0 | | 9x-36x+5x-20= | | .50x+6-3x+.50=3.5 | | .66-6h=2.16 | | x(28+4x)=72 | | 9h+22=-5h-17 | | 12a-64=-64 | | 5(c+5)=3(c+11) | | 9(m+3)=3m-21 | | -5.55=0.3x-2.5-2.6 | | .25x+125-.10=20.45 | | 11x^2-66x=0 | | 22-w/3=-7 | | 7x-y+z-w=4 | | 2(x-11)=6(x-3) | | (9x+4)-(-3x+8)= | | 5(x+1)-5(x+8)=-2.333333333 | | 5(x+1)-5(x+8)=-2.3333333333 | | B+34=3B | | -4c^2+8c-4=0 | | e+34=3e | | 28+X=3(11+X) | | 2(x+4)-5(x-7)=-2(x-1) | | 8t^2+59t-40= | | 8t^2-77t+45= | | 25+5=-15 | | 8t^2-77+45= | | 0=3x^4-4x^2+81 |